WHAT DRIVES STUDENTS TO ORDER IN? A TAM-MODIFIED MODEL AT FOOD DELIVERY SERVICE PLATFORMS - Iqromi, Salsabillah; Putra, Yuniarti Hidayah Suyoso (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study aims to analyze the factors that influence the use of Food Delivery Service (FDS) platforms by students of the Faculty of Economics, UIN Maulana Malik Ibrahim Malang, using a modified Technology Acceptance Model (TAM) framework. The variables examined include Perceived Ease of Use, Perceived Usefulness, Social Influence, and Service Quality, as well as their influence on Attitude Toward Using, Behavioral Intention to Use, and Actual Use. This study employs a quantitative approach using the SEM-PLS method. The analysis results indicate that Service Quality significantly influences Attitude Toward Using, which in turn affects Behavioral Intention to Use and Actual Use. Meanwhile, Perceived Ease of Use, Perceived Usefulness, and Social Influence do not show significant direct effects. These findings emphasize the importance of service quality and user attitude as key factors in driving intention and actual behavior in using the FDS platform.